Exploring the Effect of Differences in the Acoustic Correlates of Adults' and Children's Speech in the Context of Automatic Speech Recognition. (21st March 2010) - Ghai, Shweta; Sinha, Rohit
Abstract : This work explores the effect of mismatches between adults' and children's speech due to differences in various acoustic correlates on the automatic speech recognition performance under mismatched conditions. The different correlates studied in this work include the pitch, the speaking rate, the glottal parameters (open quotient, return quotient, and speech quotient), and the formant frequencies. An effort is made to quantify the effect of these correlates by explicitly normalizing each of them using the already existing techniques available in literature. Our initial study done on a connected digit recognition task shows that among these parameters only the formant frequencies, the pitch, and the speaking rate affect the automatic speech recognition performance. Significant improvements are obtained in the performance with normalization of these three parameters. With combined normalization of the pitch, the speaking rate, and the formant frequencies, 80% and 70% relative improvements are obtained over the baseline for children's speech and adults' speech recognition under mismatched conditions.